2000
DOI: 10.1126/science.288.5464.349
|View full text |Cite
|
Sign up to set email alerts
|

Language Discrimination by Human Newborns and by Cotton-Top Tamarin Monkeys

Abstract: Humans, but no other animal, make meaningful use of spoken language. What is unclear, however, is whether this capacity depends on a unique constellation of perceptual and neurobiological mechanisms, or whether a subset of such mechanisms are shared with other organisms. To explore this problem, we conducted parallel experiments on human newborns and cotton-top tamarin monkeys to assess their ability to discriminate unfamiliar languages. Using a habituation-dishabituation procedure, we show that human newborns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
297
0
7

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 392 publications
(314 citation statements)
references
References 20 publications
10
297
0
7
Order By: Relevance
“…However, the pairs with which the monkeys had most difficulties were also the ones that led to the longest reaction times in humans, suggesting comparable analysis mechanisms (Sinnott 1989). Ramus et al (2000) found that both cotton-top tamarins as well as human babies were able to discriminate speech sentences in two different languages, but not if the sentences were played backwards (Ramus et al 2000). Conversely, Hopp et al (1992) found that Japanese macaques were less accurate than human listeners in a discrimination task along a continuum of synthetic 'coos' varying on the temporal position of the f0 peak-although humans also generally perform better at discrimination tasks involving lower-level acoustic cues .…”
Section: Are Conspecific Vocalizations Special?mentioning
confidence: 99%
“…However, the pairs with which the monkeys had most difficulties were also the ones that led to the longest reaction times in humans, suggesting comparable analysis mechanisms (Sinnott 1989). Ramus et al (2000) found that both cotton-top tamarins as well as human babies were able to discriminate speech sentences in two different languages, but not if the sentences were played backwards (Ramus et al 2000). Conversely, Hopp et al (1992) found that Japanese macaques were less accurate than human listeners in a discrimination task along a continuum of synthetic 'coos' varying on the temporal position of the f0 peak-although humans also generally perform better at discrimination tasks involving lower-level acoustic cues .…”
Section: Are Conspecific Vocalizations Special?mentioning
confidence: 99%
“…Evidence for such innate constraints is quite strong. In the first month of life, infants prefer intonated speech to syllable lists, show a right ear and left-hemisphere brain advantage for processing speech-like stimuli, and can discriminate nonnative languages across, but not within, prosodically defined linguistic families (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, neonates can discriminate utterances from 2 languages of different rhythmic classes (6)(7)(8). Two-to four-month-olds learn to distinguish languages belonging to the same rhythmic class (4,9).…”
mentioning
confidence: 99%